Application of The Penta Helix Concept to Develop Mice Industry Creativity and Innovation - Fitriatunnisa Shabrina (Politeknik Siber Cerdika Internasional, 2023)
The MICE industry is a driving force for the creative industry, through meeting activities, Incentive Tours, Conferences and Exhibitions can be the initial capital to encourage creative thinking in formulating concepts and so on. Of the many MICE potentials that exist in Cirebon City, there are several obstacles faced by the MICE industry, including: 1) Event creativity is still minimal, 2) Budgeting and marketing strategies are not yet optimal including MICE promotion, 3) Lack of socialization of MICE activities. 4) There is no development strategy planned by the government that can indicate the direction to be taken in the development of the MICE Industry, 5) Lack of human resource education (HR); 6) Weak transport, capital and tax policies; 7) Lack of research on MICE. This study aims to determine the application of the Penta Helix concept in the development of creativity and innovation in the MICE industry in Cirebon city. Data collection in this study took from primary data and secondary data. Primary data were obtained from observations and informants related to those managing the tourism sector and the Creative Economy in Cirebon City, especially the MICE Industry. Primary data was obtained using three data collection techniques, namely (1) observation; (2) In-depth interviews (Indept interview); and finally (3) Library Studies. While secondary data can be obtained from collecting data sourced from the library, policy studies and government institutions. All data obtained will be analyzed in three stages, namely data reduction, data display/presentation of data and conclusion.